Picture-based insurance project: Stakeholder perspectives from India - Rajeesh, Sangeetha (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Climate change and increasing weather risks, together with the existing production and price uncertainties, are making agriculture more challenging for smallholder farmers in India. Existing crop insurance products are yet to provide farmers with timely financial and livelihood protection. The International Food Policy Research Institute (IFPRI) and partners are testing picture-based insurance (PBI) as an innovative approach to strengthen crop insurance across three states – Haryana, Odisha, and Tamil Nadu since 2018. The aim of PBI is to provide smallholder farmers with low cost, timely and accurate crop insurance by using the novelty of smartphone and remote sensing technologies, sometimes bundled with agricultural credit and advisories. This paper evaluates the outcomes of PBI in India from partner-stakeholder perspectives. The outcome evaluation identifies, describes, verifies, and analyses changes brought about by PBI, including changes in knowledge, attitude, behaviour, and practices that occur at partner-stakeholder level. The study finds changes in basis risk discourse with partnerstakeholders i.e., how they think, talk and act on the subject has changed. Another significant outcome is agricultural finance and crop advisory partners adopting key innovations developed through PBI research. Evidence indicates basis risk outcomes from PBI changed the attitude and behavior of partners, stakeholders, and farmers toward crop insurance in general, with PBI gaining acceptance as a product for accessible and accurate insurance. Together, these outcomes contributed to improved trust-relations for crop insurance. Scaling out PBI through the Pradhan Mantri Fasal Bima Yojana is recommended. For future research, integrating PBI within farmer producer organizations across agro-ecological and socio-economic landscapes, expanding into high value agriculture can be a sustainable approach.